Atlas of Esophagus and Stomach Pathology - Owens, Scott R.; Appelman, Henry D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Atlas of Esophagus and Stomach Pathology provides an image-based resource for those studying normal histology of the upper gastrointestinal tract, as well as the microscopic manifestations of developmental abnormalities, toxic insults, infectious diseases, inflammatory and autoimmune conditions, and neoplasia in the esophagus and stomach. Because modern gastrointestinal pathology practice centers on specimens obtained during endoscopic examination, the atlas focuses on biopsy pathology, providing “real-world” microscopic images and ancillary diagnostic studies for most commonly-encountered abnormalities and diseases affecting these two organs. The book is supplemented with endoscopic and special study images.   Authored by nationally and internationally recognized pathologists, Atlas of Esophagus and Stomach Pathology is a valuable tool for both pathologists-in-training seeking to make “new acquaintances”, and practicing surgical pathologists in need of a quick visual reference in recalling “old friends” in the world of diagnostic gastrointestinal pathology.
Normal Histologic Anatomy and Common Variations -- General Microscopic Changes -- Noninfectious Inflammatory Conditions -- Infectious Esophagitis and Organisms -- Benign Squamous Proliferations -- Squamous Intraepithelial Neoplasia -- Invasive Squamous Cell Carcinoma -- Unusual Carcinomas, Including Squamous Variants -- Nonneoplastic Barrett's Mucosa -- Dysplasia and Dysplasia Mimics in Barrett's Mucosa -- Invasive Adenocarcinoma in Barrett's Mucosa -- Mesenchymal and Melanocytic Proliferations -- Esophageal Odds and Ends -- Gastric Cardiac Mucosa -- Normal Biopsy Anatomy/Histology and General Changes -- General Microscopic Changes and Findings to Ignore -- Structural Abnormalities/Heterotopias -- Vascular Abnormalities -- Toxic and Medication-Induced Conditions -- Noninfectious Inflammatory and Systemic Diseases Affecting the Stomach -- Infectious Diseases and Organisms -- Hyperplastic/Metaplastic Conditions -- Benign Tumors and Polyps -- Epithelial Dysplasia and Adenomas -- Carcinoma of the Stomach -- Carcinoid Tumor of the Stomach -- Mesenchymal Neoplasms -- Hematolymphoid Neoplasms -- Gastric Metastases.
Keywords: Pathology; Pathology